The impact of digital transformation on the business efficiency of the New York Times - Joško Lozić; Katerina Fotova Čiković (UTMS Journal of Economics, 2021)
The purpose of this study is to analyse the business performance, i.e. business efficiency of the New York Times in the process of its digital transformation. The main methodology used in this study is the regression analysis. This research focuses on the financial efficiency of the New York Times in combination with the trend of the number of users. On one hand, the financial stability of the business is investigated, and on the other, the transformation and trend of the number of users are analysed. The comparison of the research results is aimed at answering research questions in the context of the impact of digital transformation on the business efficiency of a corporation. The findings serve as the basis for decision-making in the process of digital transformation of the analysed corporation, and the model can also be used by other players in the media industry (or any other industry) in the process of their digital transformation. Furthermore, this study argues the benefits from the digital transformation of a business and the impact the COVID-19 pandemic had on the acceleration of the digital transformation processes in organizations across the globe.
Keywords: L14; L81; L82; L86; 330; digital transformation; business efficiency; New York Times; media industry; platform economy